COMPARISON BETWEEN APRIORI AND FP-GROWTH ALGORITHMS ON INVENTORY MODEL OF ITEM AVAILABILITY - Radhiatul Husna; Yomei Hendra; Muhammad Imam Akbar (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
In this study, it will be discussed the comparison between apriori and fp-growth algorithms on aninventory model of item availability. The research about this topic becomes important and interestingto be studied because it illustrates the implementation of applied mathematics by constructing thematematical model, namely an inventory model of item availability. Then, the model will be solved byusing apriori and fp-growth algorthms related to the application of probability theory. In this case,apriori and fp-growth algorithms are used to specifythe pattern of dependency relationships between an item and other items so that the probability ofitem purchase based on other goods can be discovered. Moreover, the number of items which shouldbe provided by a seller in a shop or a supermarket can be calculated. In order to figure out the outputof this research which is the analysis of the comparison between apriori and fp-growth algorithms onthe inventory model of item availbility, then choosing and categorizing kinds of items based on thesales, using the apriori and fp-growth algorithms, constructing the model, solving and interpreting itare established